2016
DOI: 10.1016/j.scitotenv.2016.03.152
|View full text |Cite
|
Sign up to set email alerts
|

Residential metal contamination and potential health risks of exposure in adobe brick houses in Potosí, Bolivia

Abstract: Potosí, Bolivia, is the site of centuries of historic and present-day mining of the Cerro Rico, a mountain known for its rich polymetallic deposits, and was the site of large-scale Colonial era silver refining operations. In this study, the concentrations of several metal and metalloid elements were quantified in adobe brick, dirt floor, and surface dust samples from 49 houses in Potosí. Median concentrations of total mercury (Hg), lead (Pb), and arsenic (As) were significantly greater than concentrations meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Using 123 and 26 hair samples collected from children from non-industrial urban and smelter areas respectively, the authors found higher risk of exposure for smelter community children indicated by higher Z score (p<0.001) (Goix et al, 2011a). In Potosi, another study sampled adobe brick, dirt floor, and dust from mining and control sites showing positive correlations between adobe brick and dirt floor samples for total As (r = 0.57) (McEwen et al, 2016). Results also suggested an ingestion rate at or above 200 mg/day of combined soildust particles containing As in 1 and 6 year old children to be associated with potential health risk in mining communities (McEwen et al, 2016).…”
Section: Risk Assessmentmentioning
confidence: 97%
See 1 more Smart Citation
“…Using 123 and 26 hair samples collected from children from non-industrial urban and smelter areas respectively, the authors found higher risk of exposure for smelter community children indicated by higher Z score (p<0.001) (Goix et al, 2011a). In Potosi, another study sampled adobe brick, dirt floor, and dust from mining and control sites showing positive correlations between adobe brick and dirt floor samples for total As (r = 0.57) (McEwen et al, 2016). Results also suggested an ingestion rate at or above 200 mg/day of combined soildust particles containing As in 1 and 6 year old children to be associated with potential health risk in mining communities (McEwen et al, 2016).…”
Section: Risk Assessmentmentioning
confidence: 97%
“…In Potosi, another study sampled adobe brick, dirt floor, and dust from mining and control sites showing positive correlations between adobe brick and dirt floor samples for total As (r = 0.57) (McEwen et al, 2016). Results also suggested an ingestion rate at or above 200 mg/day of combined soildust particles containing As in 1 and 6 year old children to be associated with potential health risk in mining communities (McEwen et al, 2016).…”
Section: Risk Assessmentmentioning
confidence: 99%
“…Workplace exposure contributes substantially to the burden of multiple chronic respiratory diseases, such as IPF, for instance, has a population-attributable fraction of 26% ( 34 ). In addition to the high ILD burden, participants in a study living in proximity to mining sites near Potosi, Bolivia, had higher frequencies of hypertension, hematuria, and ketonuria, and the majority of adobe brick houses in Potosi, Bolivia, contained concentrations of bio-accessible Pb and As, which represent a potential health risk ( 35 , 36 ). Therefore, effective measures are urgently required to protect residents from contaminated environments.…”
Section: Discussionmentioning
confidence: 99%
“…Mining activity contributes to the contamination of water (French et al, 2017;Salvarredy-aranguren et al, 2008), soil (Garrido et al, 2017;Hagan et al, 2011), and aerosols (Goix et al, 2016(Goix et al, , 2011. These contaminations directly threaten the environmental stability (Guédron et al, 2017;Monroy et al, 2014) and represent a potential health hazards for the local population (Barbieri et al, 2011;Goix et al, 2016Goix et al, , 2011Mcewen et al, 2016;Stassen et al, 2012). Besides the contamination effects, mining activity also contributes to the decrease in TWS.…”
Section: Additional Role Of Mining Activitymentioning
confidence: 99%